Biosynthesis and Molecular Genetics of Fungal Secondary Metabolites - Martín, Juan-Francisco.; García-Estrada, Carlos; Zeilinger, Susanne; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This volume describes the more relevant secondary metabolites of different fungi with current information on their biosynthesis and molecular genetics. Bolstered with color illustrations and photographs, the book describes the possible application of molecular genetics to directed strain improvement in great detail. The needs for future developments in this field are also discussed at length.   Written by authorities in the field, Biosynthesis and Molecular Genetics of Fungal Secondary Metabolites provides a cutting-edge perspective on fungal secondary metabolism and underlying genetics and is a valuable resource for scientists, researchers, and educators in the field of fungal biology.
Valuable Secondary Metabolites from Fungi -- Penicillins -- Cephalosporins -- Cyclosporines: Biosynthesis and Beyond -- Aflatoxin Biosynthesis: Regulation and Subcellular Localization -- Roquefortine C and Related Prenylated Indole Alkaloids -- Ochratoxin A and Related Mycotoxins -- Carotenoids -- Astaxanthin and Related Xanthophylls -- Gibberellins and the Red Pigments Bikaverin and Fusarubin -- Fusarins and Fusaric Acid in Fusaria -- Lovastatin, Compactin, and Related Anticholesterolemic Agents -- Meroterpenoids -- Ergot Alkaloids -- Fungal NRPS-dependent Siderophores: from Function to Prediction.
Keywords: Cell biology; Microbiology; Plant genetics; Plant biochemistry; Cell Biology; Microbiology; Plant Genetics and Genomics; Plant Biochemistry